Mechanical study and equations for gravity flow pipe liners stretching across ring fractures or joints under shear action - Zhai, Kejie; Moore, Ian D. (Ocean engineering, 2024)
Cured-in-place-pipe (CIPP) liners have been widely used in rehabilitation of gravity flow pipelines. However, the host pipe rehabilitated by the CIPP liner may be subject to shear force and shear displacement at the joint. In this study, a finite element model of a rigid host pipe with liner under shear action is established and used to study the resulting behaviour. Controlling factors such as the gap spanned by the liner between host pipes across the joint, diameter, the liner thickness, the elastic modulus of the liner, and the coefficient of friction between host pipe and liner are studied. The liner stress, displacement, and shear force are reported. Shear stiffness and stress equations are then fitted based on 286 data points. The results show that the maximum stress on the inner surface of the liner occurs at the shoulder and haunch, and the maximum stress on the outer surface occurs at the springline. The inner surface stresses at the crown and invert decrease with increases in liner-host pipe friction, but increase at the shoulder and haunch. Coefficient of Friction has almost no effect on the stresses that develop on the outside surface of the liner. •An FE model for liners stretching across joints under shear action is established.•Controlling factors are studied.•Shear stiffness and stress equations are then fitted based on 286 data points.•Friction coefficient has almost no effect on the liner stresses.